Everglow - Nandita Bose (Ruba publication, New Delhi, 2019)
When her father's unexpected death renders Disha homeless, she is brought to Kolkata by her father's best friend, toive with them. Home is now a rambling joint family where there are more young men than Disha has even known in all herife. A far cry from the simplicity of herife back in Hamirpur, Disha sets about trying to fit in with the rhythms of this household and its members. And then she meets the second son and star of the family"Siddhant. Sid is theead guitarist of the rock band, Derozio Dreams, and when he discovers that Disha is a classically trained vocalist, he brings her to his band to enhance their fusion repertoire. Music becomes their meeting ground and with Sid involving himself in her initiation into the band, they draw closer, to the chagrin of some family members, especially his mother, who thinks Disha, the outsider, has transgressed. When Disha's elder sister wants her to come back to Hamirpur to be seen as a prospective bride for her husband's cousin, Disha's fate hangs by a slender thread. Will the promise ofove and the music that Disha and Sid make together triumph over all odds?
Keywords: Fiction; Romance